Morphological and biochemical identification of Ralstonia solanacearum strains in ginger (Zingiber officinale Roscoe) wilt disease - Natalia, Kezia; Setiawan, Andree Wijaya; Jayanti, Ruth Meike (Jurnal Ilmiah Pertanian, 2024)
The Ralstonia solanacearum Species Complex (RSSC) is a significant plant pathogen affecting various agricultural commodities, including ginger. Understanding the distribution and characteristics of RSSC in ginger plants is crucial for effective disease management. This study aims to determine the distribution of RSSC in ginger plants and identify the pathogen through morphological and biochemical characterization. The research was conducted in Banyubiru and Getasan districts, Semarang Regency, Indonesia. The study involved purposive sampling, isolation, and purification of isolates, followed by morphological characterization through observation and biochemical characterization using Gram staining with KOH, oxidase test, arginine activity test, hypersensitivity test, bacterial density calculation, Koch's postulates, and biovar characterization. Three isolates from Banyubiru displayed typical morphological characteristics of RSSC, including round, mucoid colonies with red centers and white edges on TZC medium, and rod-shaped bacterial cells. Biochemical characterization identified these isolates as RSSC strains biovar 3 and 4, capable of causing bacterial wilt in ginger plants. The study confirmed the presence of bacterial wilt in ginger in Banyubiru district. The findings reveal the spread of bacterial wilt caused by RSSC in ginger plants in Banyubiru, Semarang Regency. There is a need for measures to control the potential spread of RSSC in the surrounding host plant areas in Tlumpak Village, Banyubiru district.